Inskrypcja filadelfijska starożytnym świadectwem stosunku do życia poczętego - Sawa, Robert (Vox Patrum, 2008)
The article above contains a Polish translation and some notes on an ancient text known as Philadelphian inscription. Found at the beginning of the 20th century among ruins of the ancient Lydian Philadelphia (now Turkish Alaęehir), carved on a blue marble stele, with no doubt originally placed in front of an ancient chapel, serving also as a meeting place of a smali religious and philosophical community headed by a man called Dionysios. The inscription gives some principles of purity to be followed by the guests of the chapel, with ethical and social issues involved, e.g. chastity of marriage, related both to man and woman, free and slave, as far as condemn of application of any poisonous or abortive substances. The most interesting fact about the text of the inscription is an approval of a fetus as a child, a human being whose life should be protected, and abortion must be actually treated as a kind of homicide. It is known also as the first written evidence of the Hippocratic oath’s influence in the ancient world.